DNA barcoding reveals an unexpected distribution of two Megaleporinus species in the La Plata Basin system - Coronel, Florencia Paola; Loretán, Gisela; Sanchez, Sebastián; Silva, Natalia; Pacheco-Sierra, Gualberto; Brancolini, Florencia; Aichino, Danilo; Vargas, Facundo; Scarabotti, Pablo; Espínola, Luis; Pavanelli, Carla Simone; Rueda, Eva Carolina (Frontiers in Ecology and Evolution, 2025)
IntroductionMegaleporinus obtusidens, also known as "boga," is a freshwater teleost fish species widely distributed across South America with significant commercial value in Argentina and Brazil. Fishers, particularly those in the lower Paraná River, frequently classify the fish they catch as M. obtusidens. Despite various approaches, including cytogenetics, molecular data, and morphological analysis, the taxonomic classification of the boga fish remains debated among researchers, resulting in discrepancies in the literature.MethodsThis study aimed to assess the diversity of specimens captured in the La Plata River Basin, initially classified as Megaleporinus obtusidens by fishers, using DNA barcoding. The mitochondrial COI marker was employed to explore species assignment and genetic diversity in Megaleporinus, a genus with high commercial exploitation in the southern area of the La Plata Basin.ResultsOur findings indicate that some boga samples, previously identified as M. obtusidens, are actually M. piavussu. We also observed significant differences in the geographic distribution, diversity, and genetic structure between the two species.DiscussionThese results highlight the importance of studying the ecology of each species separately. Proper resource management, based on accurate species identification, is critical for the conservation of ichthyofauna in the region.